Ketegaran Wanita Hamil di Luar Nikah dalam Menghadapi Tekanan Keluarga dalam Novel Menjaring Mata Angin - Suratno, Pardi; Nugroho, Yusro Edi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
Menjaring Mata Angin is a novel by Triman Laksana. In the novel, the character Pertiwi is shown to be pregnant without having sex with men. Throughout her life, Pertiwi has experienced a lot of mental and physical stress due to her pregnancy. This article attempts to describe family domination or pressure on Mother Earth, namely pressure from father, mother, and siblings. In general, they cannot accept the condition of Pertiwi which is considered to have dishonored their extended family. The research data is in the form of words, sentences, paragraphs in Menjaring Mata Angin which contains domination or pressure exerted by the family on Mother Earth. This study uses intrinsic literary theory, namely examining things that are in literary works autonomously or objectively. The method used is the method of observing and noting. After reading in depth, the research data is recorded which will be used as material for analysis. After that the data is interpreted with inductive descriptive techniques to reach research conclusions. From the results of the study, it can be stated that the family put pressure on Pertiwi who got pregnant out of wedlock. However, Pertiwi remained strong in enduring suffering and was determined to protect the fetus she was carrying. It is the rigidity of women who become pregnant out of wedlock in maintaining the pregnancy that is the pressure in this study.